Mekanisme Survival dan Kesejahteraan Guru Sekolah Dasar: Studi Kualitatif di SDN Campaka - Safira, Nadiyah Aulia; Labah, Rahma Nur; Asri, Razi Fauziah; Ersakta, Arkan Abhirama; Salsabila, Aprilia; Kharima, Nadya (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study explores the survival mechanisms employed by teachers at SDN Campaka, Margamukti Village, in overcoming challenges and utilizing social support to sustain their professional roles.Method – A qualitative research approach was used, incorporating one-session interviews, two-day observations, and document analysis. Data were analyzed using Creswell’s method, including data preparation, coding, narrative presentation, interpretation, and verification. Participants were selected through purposive sampling, consisting of two civil servant teachers (PNS), one government contract teacher (PPPK), and one honorary teacher. Findings – The findings reveal that teachers at SDN Campaka adopt multiple survival strategies to navigate professional challenges. They assume generalist roles beyond teaching, including administrative duties and extracurricular management. Social support, particularly from colleagues and the school community, plays a crucial role in strengthening their coping mechanisms, fostering resilience, and sustaining motivation. Research Implications – This study underscores the importance of psychological well-being and workplace recognition in enhancing teacher motivation and instructional quality. It highlights key strategies such as discipline, adaptability, and engagement in positive activities to maintain a healthy work-life balance. Addressing the unique needs of non-permanent teachers is essential to improving their professional satisfaction and overall effectiveness in the classroom. However, the study is limited to a small sample in one school, requiring further research for broader generalization.